Tingkat Kerapuhan dan Daya Terima Biskuit yang Disubstitusi Tepung Daun Kelor ( Moringa oleifera ) - Azizah, Aprillia Ayu; , Rusdin Rauf, S.TP., M.P; , Dyah Widowati, SKM (2015)
Introduction : According to Riset Kesehatan Dasar (Basic Helath Research) in 2013, the prevalence of malnutrition in toddlers in Indonesia had reached up to 19,6%. Based on the date, the malnutrition case in toddlers and babies in critical condition. It can be assumed that they have the higest possibility of malnutrition in society. It may lead to the high amount of death caused by malnutrition in toddlers and babies. Because malnutrition toddlers can be easily infected by particular viruses. Research method : This study used experimental research method with an approach called completely randomized design (CRD). Statistical test that is used in this research is the One-Way ANOVA and followed by LSD tests to determine the real difference. Result : These results indicate that the best level of fragility is from the biscuit that is substituted by 15% moringa leaves with large power required to break the biscuit is 12,4 N. A total of 4 formula substitutions required to make the products, which have the higest value based on the acceptability power is Moringa leaf powder biscuits that substituted and controlled (95% wheat flour : 5% Moringa leaf powder). Conclude : The study concluded that there is a substitution effect of Moringa leaf powder to the level of fragility and acceptability of Moringa leaves biscuits.